AUTOCRATIC LEADERSHIP STYLE AND ORGANIZATIONAL CHANGE ON PERFORMANCE DURING PANDEMIC - Asno, Suparti; Sary, Fetty Poerwita (TRIKONOMIKA, 2023)
The COVID-19 pandemic that is overtaking the world, particularly Indonesia has undoubtedly changed business scenarios and conditions, requiring practical and strategic approaches to bring enterprises back from the verge of disaster. In order to overcome a pandemic situation like this, a leader with an autocratic leadership style is required, as well as an organizational change to make the company survive and adapt to existing changes in order to maintain the company's survival so that employee performance remains good and optimal. The goal of this research was to see if there was a relationship between autocratic leadership style and organizational transformation and the performance of “PT ABC” workers during the pandemic. The sample technique is non-probability sampling and uses 100 respondents from “PT ABC” employees. The results of this research show that the autocratic leadership style and organizational change have a posittive and significant effect on employee performance during the pandemic at “PT ABC” company.